Strampelli's osteo-odonto-keratoprosthesis. Clinical and histological long-term features of three prostheses. Issue 4 (April 1992) - Ricci, R.; Pecorella, I.; Ciardi, A.; Della Rocca, C.; Di Tondo, U.; Marchi, V.
Abstract : The histological features are reported of osteo-odonto-acrylic laminae removed from three patients who for differing underlying causes received Strampelli's osteo-odonto-keratoprostheses (OOK) 20, 16, and 12 years previously. It appears that preservation of the alveolar-dental ligament plays a definitive role in the maintenance of the prosthesis. If this tissue undergoes necrosis as a consequence of an inflammatory disease the implanted material is eventually lost. However when no such event occurs the OOK is well preserved and well tolerated even 20 years after implantation.